2007
DOI: 10.1176/appi.ajp.2007.06071239
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Use of Mental Health Services by Persons With Serious Mental Illness: Do Spanish-Speaking Latinos Differ From English-Speaking Latinos and Caucasians?

Abstract: This study suggests that for Latinos, preferred language may be more important than ethnicity in mental health service use. Future studies comparing mental health use may need to differentiate between Spanish- and English-speaking Latinos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 44 publications
3
50
0
Order By: Relevance
“…Particular attention should be paid to including these when comparing ethnic groups, because ethnic differences in adherence have been found to disappear when, for example, income was accounted for (73). As previously noted (56, 65), preferred language may be a better predictor of health patterns than ethnicity. It is essential to include adequate numbers of Spanish-speaking as well as bilingual and English-speaking patients and clinicians in future research to better understand these relationships.…”
Section: Discussionmentioning
confidence: 51%
“…Particular attention should be paid to including these when comparing ethnic groups, because ethnic differences in adherence have been found to disappear when, for example, income was accounted for (73). As previously noted (56, 65), preferred language may be a better predictor of health patterns than ethnicity. It is essential to include adequate numbers of Spanish-speaking as well as bilingual and English-speaking patients and clinicians in future research to better understand these relationships.…”
Section: Discussionmentioning
confidence: 51%
“…We propose an additional path between English proficiency and services use [22, 23]. That is, we expect that the set of cultural and social factors associated with English proficiency will have an independent effect on hospitalizations and costs beyond their effects on medication adherence.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with our prior research, we use a client’s preferred service language as a proxy for limited English proficiency status [22, 23]. Clients report their preferred language for receiving services at admission to each service, and we use a client’s revealed preference for service language as a proxy for English proficiency.…”
Section: Methodsmentioning
confidence: 99%
“…This contrasts with previous work which has shown that individuals with poor language proficiency have higher rates of depression, anxiety, and substance abuse compared to those with good to excellent language proficiency. [2][3][4] However, in these studies participants had at least limited English skills and data collection took place in the United States where there is a pre-eminence of English as an "official language". In contrast, the current study was unable to assess English or French language proficiency and took place in Canada where two official languages exist.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some linguistic minority groups have been shown to have an increased risk for poor mental health. [2][3][4] However, it should be noted that the relationship between language and mental health outcomes has been inconsistent. [5][6][7][8] This may be attributed to the fact that research occurring in Canada and the United States has almost exclusively focused on visible minority groups or immigrants as a proxy for language use.…”
mentioning
confidence: 99%